THE RELATIONSHIP BETWEEN MOTHER'S EDUCATION LEVEL WITH EXCLUSIVE BREASTFEEDING IN BAE VILLAGE, BAE DISTRICT, KUDUS REGENCY - Sukma Wardani; Rina Novita (Jurnal Profesi Bidan Indonesia, 2022)
Background: The importance of exclusive breastfeeding for babies had been stated on International guidance. By the current development, the existence of women on many sectors will increase. The level of mother’s education and knowledge can support the achievement of breastfeeding for babies too. The percentage of breastfeeding in Kudus regency just 13,9%, and the lowness is in Bae subdistric (8%).Purpose: to know the relationship between level of mother’s education and exclusive breastfeeding.Method: Kind of this research design and retrospective approach with level of education as independent variabel, and exclusive breastfeeding as dependent variabel, uses 85 population and the technique on getting sample is total sampling and chi square test as statistical experiment.Results: The result was got p value 0,044 < α = 0,05 (significant standard) used chi square test, so Ho refused and Ha recived. Then there was relationship between education level and exclusive breastfeeding. Based on the research can be concluded if mother has level of education 3.2 fold can increase the achievement of exclusive breastfeeding. Conclusion: Based on the research, it can be concluded that mothers who have higher education 3.2 times increase the success of exclusive breastfeeding